A European Perspective on Recent Trends in U.S. Climate Policy - Ulf Moslener; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Without participation of the United States, the world?s largest emitter of greenhouse gases, mitigation of global climate change seems hardly conceivable. Despite the U.S. rejection of the Kyoto Protocol and the reluctance of the Bush administration to engage in Post-Kyoto negotiations, recent developments suggest that the U.S. position towards climate policy might change in the medium run. This study provides an overview on current trends in U.S. climate policy. Besides the main elements of national climate policy proposals and state-level initiatives the climate contents in the U.S. presidential candidates? agendas are outlined. Based on this overview recent trends in U.S. climate policy are related to the European approach to combat climate change. Furthermore, we elaborate on the aspects which may be important for Europe to design its own domestic and international climate policy in order to achieve the long-term goal of stabilizing greenhouse gas concentrations.
Keywords: Q58; N50; K32; H73; 330; environmental regulation; climate policy; emissions trading; Klimaschutz; Emissionshandel; USA; EU-Umweltpolitik; EU-Staaten